Explorations in the English Language: Middle Ages and Beyond - Esquibel, Joanna,Wojtys, Anna (Peter Lang GmbH, 2012)
The volume, inspired by Professor Wełna’s life-long studies in historical linguistics, brings together scholars researching topics in various fields of the history of the English language. Nine chapters devoted to different linguistic disciplines gather articles covering sound and spelling changes, historical word-formation processes, selected semantic domains, and manuscript variants. In the broader perspective the book addresses the history of linguistic thought with authors incorporating different tools of analysis in historical research.
10.3726/978-3-653-02361-9
Keywords: Bibliographie; Aufsatzsammlung; Wełna; Jerzy; Mittelenglisch; Englisch; Historische Sprachwissenschaft